2020
DOI: 10.3399/bjgpopen20x101134
|View full text |Cite
|
Sign up to set email alerts
|

Look who’s talking now: Cancer in primary care on Twitter. An observational study

Abstract: Twitter is a microblogging platform that helps share information. It is a dynamic tool that has been embraced by many user types including consumers and health care professionals. Currently, there are no data on how cancer in primary care features on Twitter. To explore the type of users and information shared about cancer in primary care on Twitter. Descriptive exploratory study of publicly available Twitter data. Tweets were searched between July 2015 and June 2017 for ‘GP’, ‘general practice’, ‘primary care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…Miller et al [ 154 ] combined the Health Belief Model to encode and analyze posts from patients with breast cancer. In addition, 2 (3.1%) studies [ 104 , 142 ] used quantitative content analysis to measure the frequency of content in papers in the entire sample and combined qualitative content analysis to facilitate the classification of information by source and content; 2 (3.1%) studies [ 86 , 144 ] combined machine coding and manual coding and compared their effectiveness; and in 1 (1.6%) study [ 59 ], the post content was preclassified and evaluated according to 8 aspects, such as emotion and media format, without mentioning the traditional content analysis steps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Miller et al [ 154 ] combined the Health Belief Model to encode and analyze posts from patients with breast cancer. In addition, 2 (3.1%) studies [ 104 , 142 ] used quantitative content analysis to measure the frequency of content in papers in the entire sample and combined qualitative content analysis to facilitate the classification of information by source and content; 2 (3.1%) studies [ 86 , 144 ] combined machine coding and manual coding and compared their effectiveness; and in 1 (1.6%) study [ 59 ], the post content was preclassified and evaluated according to 8 aspects, such as emotion and media format, without mentioning the traditional content analysis steps.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally believed that compared to computer-aided analysis, manual analysis has higher accuracy and is superior in handling subtle concepts such as ideology, concepts, value, and meaning [173]. In addition, by reviewing 2 papers [104,142] that used quantitative content analysis, we found that similar to computer-aided analysis, content analysis can also identify the essential features of content to which statistics can be easily applied through quantitative analysis of information, thereby achieving a more accurate understanding of information [174].…”
Section: Principal Findingsmentioning
confidence: 99%
“…All posts were purchased from a professional service provider during the research timeframe. According to the recommendations of social media researchers [ 58 , 59 ], the researchers opted for the assistance of Podargos Technologies. The research period was set between June 08 and July 18, 2019 for the Jeddah Season, and between October 11 and December 30, 2019 for the Riyadh Season.…”
Section: Methodsmentioning
confidence: 99%
“…Tweeting has been utilized and discussed concerning various medical sub-domains including vascular surgery,[ 1 ] oncology/cancers,[ 6 7 ] cardiology,[ 8 ] psychiatry,[ 2 ] breast cancer prevention[ 9 ] and bowel disease. [ 10 ] Although Twitter usage in pathology context has been published,[ 11 12 13 14 15 16 17 18 ] but its usage OHC context is still in infancy and needs to be documented and utilized fully.…”
Section: Tweeting and Oral Health Carementioning
confidence: 99%